Type designation of the Linnaean name Theligonum cynocrambe (Rubiaceae, Theligoneae) - Ferrer-Gallego, Pedro Pablo (Phytotaxa, 2018)
The lectotype of the name Theligonum cynocrambe Linnaeus (1753: 993) is designated. Previously, a type was selected by Ali in 1977 from a specimen kept at LINN. However, this typification is rejected since there are original elements that may contribute to a correct lectotypification of the name. Therefore this choice is ineffective and should be rejected. An illustration from Bauhin (1620) is designated as the lectotype in this work. On the other hand, in order to avoid any ambiguity in the interpretation of the lectotype, an epitype is also selected.